Cortical abnormalities on MRI: what a neurologist should know. Issue 4 (28th April 2015) - Renard, Dimitri; Castelnovo, Giovanni; Bouly, Stephane; Le Floch, Anne; Waconge, Anne; De Verdal, Marie; Thouvenot, Eric
Abstract : Cerebral cortical lesions develop in many disorders including vascular diseases, metabolic disorders, inflammatory diseases, tumours, infections and genetic disorders. In some diseases, the cortical involvement is typical and sometimes isolated, while in others the cortical lesions occur only occasionally (often alongside other typical extra-cortical lesions). In this review, we discuss mainly the MRI characteristics of cortical lesions encountered in different disorders. From a radiological perspective, identifying the origin of a cortical lesion depends on the exact localisation of signal changes, the presence of extra-cortical lesions, the signal changes on different MRI sequences and the evolution of the radiological abnormalities over time. These must be interpreted in light of the history and clinical state of the patient, and other radiological and non-radiological examinations.